1993
DOI: 10.1172/jci116404
|View full text |Cite
|
Sign up to set email alerts
|

Importance of factor Xa in determining the procoagulant activity of whole-blood clots.

Abstract: The binding of thrombin to fibrin is thought to be an important mechanism by which thrombi exhibit procoagulant activity; however, the extent to which other procoagulants are associated with thrombi has not been previously defined. This study was designed to determine whether clotting factors other than thrombin are bound to whole-blood clots and can thereby contribute to significant procoagulant activity. Clots formed in vitro from human blood exhibited minimal thrombin activity when incubated in plasma deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
112
0
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(117 citation statements)
references
References 18 publications
4
112
0
1
Order By: Relevance
“…Abdominal aortic injury was induced in rabbits by overinflation and multiple passages of a 4F embolectomy catheter. Rabbits were killed 15 minutes or 4,8,24,48, 72, 96, or 120 hours after injury. Aortic segments were incubated ex vivo to define bound procoagulant activity.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Abdominal aortic injury was induced in rabbits by overinflation and multiple passages of a 4F embolectomy catheter. Rabbits were killed 15 minutes or 4,8,24,48, 72, 96, or 120 hours after injury. Aortic segments were incubated ex vivo to define bound procoagulant activity.…”
mentioning
confidence: 99%
“…7 Accumulation of platelets and fibrin at the site of arterial injury, even when thrombus is not grossly apparent, also mediates the progression of thrombosis by binding activated coagulation factors. 8,9 We have shown that arterial thrombi induce marked activation of the coagulation system attributable to platelet-associated Xa/Va activity and thrombin bound to fibrin. 8 However, the extent to which procoagulant factors bind to the injured vessel wall, particularly in the absence of significant mural thrombus, and the duration of procoagulant activity associated with the vascular wall after arterial injury are not well defined.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, coagulation factor Xa has been found to be adsorbed to fibrin clots and this clot-bound factor Xa may be involved in thrombin generation and be resistant to the heparindependent AT 111 inhibition [16]. In the present study, we studied the characteristics of the binding of factor Xa to fibrinogedfibrin derivatives, in a comparative evaluation with thrombin binding.…”
mentioning
confidence: 96%